Injection molding micro patterns with high aspect ratio using a polymeric flexible stamper (eXPRESS Polymer Letters)
Poor filling occurs during the injection molding process of micro- or nano- scale patterns mainly because the hot polymer melt rapidly cools and its skin quickly solidifies upon contact with the mold surface. In this study, it is proposed to use Polyethylene terephthalate (PET) film coated with patterned polyurethane acrylate (PUA) as an effective thermal barrier. It can significantly hinder heat transfer into the mold during the molding process and thus may keep the melt viscosity low for longer duration. As a result, the replication would be improved not only during the filling phase but also during the packing phase. In order to verify the validity of the use of polymeric stamper, the melt-film interface temperature was evaluated by numerical simulation. Experimental results indicated that patterns possessing widths within the range of one to tens of micrometers and a height of approximately 10 µm were successfully filled and demolded.